(untitled) (Observatorio Económico, 2011)
The economic study of family behavior began in the 1960s. This is no coincidence: the end of the baby boom in the United States coincided with a sharp rise in women’s labor force participation. By then there was already important work by sociologists and demographers, which to this day continues to complement and interact with research by economists. This line of work became popular in academia after 1973, when Gary Becker published his work on the economic theory of marriage and on the interaction between the number and the “quality” of children. Continue reading...